Rakes of the Old Court : A Novel - Caragiale, Mateiu I., 1885-1936 (Book collections on Project MUSE., 2021)
"This novel of decadence and debauchery, set in Bucharest in 1910, follows four characters through bars, brothels, and landscapes of travel and escape. The 1929 book is a classic of Romanian modernism"--